Research by the Tasmanian cosmic ray group during the International Geophysical Year - McCracken, KG; John Humble; Marcus Duldig (2009)
Systematic recording of the cosmic radiation commenced in Hobart in 1946 and at Mawson in Antarctica in 1955, making these two of the longest running cosmic ray observatories in the world. For the IGY, observations were also made at a sub-Antarctic island and near the equator, and an airborne survey of the nucleonic component was made from Geomagnetic Latitude −60°, south of Australia, to Japan and back. At Hobart there were neutron monitors, vertical and inclined muon telescopes, an ionization chamber, and two muon telescopes at 40 m of water equivalent underground. The research based on these and other observations determined the energy dependence of the Forbush and 11-year variations and concentrated, in particular, on understanding the anisotropic nature of galactic cosmic rays up to 150 GeV; the anisotropies in the onset phase of Forbush decreases; and the anisotropies in solar cosmic ray events. An investigation was initiated to calculate the trajectories and cutoff rigidities of cosmic rays in a high order simulation of the geomagnetic field. This was completed in 1959–60.